2017
DOI: 10.1002/ijc.30559
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoma cell functions modulated by NEK2 are associated with liver cancer progression

Abstract: NEK2 (NIMA-related expressed kinase 2) is a serine/threonine centrosomal kinase that acts as a critical regulator of centrosome structure and function. Aberrant NEK2 activities lead to failure in regulating centrosome duplication. NEK2 overexpression promotes tumorigenesis and is associated with poor prognosis in several cancers. Increased NEK2 expression during the late pathological stage has been detected in the Oncomine liver dataset and hepatocellular carcinoma (HCC) specimens. Elevated NEK2 protein is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 40 publications
(48 reference statements)
1
27
0
Order By: Relevance
“…Finally, NEK2 overexpression contributed to HCC tumor growth, migration, and angiogenesis by pAKT/NF-κB (factor nuclear kappa B). Regarding angiogenesis, NEK2 also induced IL-8 (Interleukin 8) expression [93].…”
Section: Nek2mentioning
confidence: 99%
“…Finally, NEK2 overexpression contributed to HCC tumor growth, migration, and angiogenesis by pAKT/NF-κB (factor nuclear kappa B). Regarding angiogenesis, NEK2 also induced IL-8 (Interleukin 8) expression [93].…”
Section: Nek2mentioning
confidence: 99%
“…Similarly, a study by Wu et al demonstrated that NKE2 overexpression can induce the resistance of hepatoma J7 or Hep3B cells to chemotherapy via upregulation of ABCC10 and the expression of Twist [29]. Additionally, abnormal activation of the p-AKT/NF-κB signaling pathway and matrix metalloproteinase-2 was found to be involved in NEK2 overexpressioninduced migration, invasion, and angiogenesis in HCC [26,29].…”
Section: Discussionmentioning
confidence: 86%
“…ABCG2, a member of ABC transporter family, is a vital element of multi-drug resistance system in cancer [47] and Lin et al demonstrated that NEK2 plays a crucial role in chemotherapeutic resistance by regulating the expression of ABCG2 in HCC cells [27]. Similarly, a study by Wu et al demonstrated that NKE2 overexpression can induce the resistance of hepatoma J7 or Hep3B cells to chemotherapy via upregulation of ABCC10 and the expression of Twist [29]. Additionally, abnormal activation of the p-AKT/NF-κB signaling pathway and matrix metalloproteinase-2 was found to be involved in NEK2 overexpressioninduced migration, invasion, and angiogenesis in HCC [26,29].…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate of HCC is usually poor due to the high probability of tumor recurrence and metastasis after treatment. We therefore urgently need to identify novel therapeutic targets and biomarkers, with the goal of developing effective strategies to improve the prognosis of HCC [5].…”
Section: Introductionmentioning
confidence: 99%